Analisis Teknik Pukulan Menyerang Jonathan Christie Dalam Pertandingan Bulutangkis All England 2024 - Syahwal Satrio Jati; Wahyu Eko Widiyanto; Bahtiar Hari Hardovi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyse the attacking stroke techniques used by Jonathan Christie in the 2024 All England tournament. The research method used is quantitative descriptive with observation techniques based on video recordings of matches from the preliminary rounds to the final. Data was collected by recording the frequency, success rate, failure rate, and point contribution of each type of attacking shot, namely smash, dropshot, drive, lob, and netting play. The results showed that smash was the most dominant technique in scoring direct points, while lob and netting play were more often used to control the tempo of the game. Overall, Jonathan was able to maintain a stroke success rate of over 85% across all types of techniques, with peak consistency shown in the final round when almost all strokes achieved an accuracy of over 90%. Based on this research, it can be concluded that the effectiveness of Jonathan Christie's game is supported by a combination of attacking shot variations, with the smash as the primary finisher and other techniques as supporting elements in creating attacking opportunities. Kata Kunci: Jonathan Christie, Attacking Shot Technique, Smash, All England 2024